Generating A Counter-Power, from the Bottom Up and to the Left (or How to Change the World, Revolutionizing Power from the Bottom Up) - Rojas, Carlos Antonio Aguirre (Pontifícia Universidade Católica de São Paulo, 2007)
The author proposes a reflection about the differences, the content and the relationships between the diverse levels and forms of power, such as state power, political power, and social power. He seeks to sketch out how a popular and subaltern counter-power can be configured, and examine the forms in which this counter-power is being produced by current anti-systematic and anti-capitalist social movements.